IMMUNOBIOCHEMICAL MARKERS OF THE DEVELOPMENT OF PULMONARY HYPERTENSION IN PATIENTS WITH CHRONIC DISEASES OF THE BRONCHOPULMONARY SYSTEM - Feruza O. Tasheva; Bakhtiyor Z. Hamdamov (Central Asian Journal of Medicine, 2024)
In light of the high prevalence of chronic nonspecific lung diseases and their significant impact on disability rates, one of the key healthcare challenges is the prevention, accurate diagnosis, and effective treatment of patients with such respiratory diseases. It is unequivocally important to pay attention to cross-disciplinary research and continue studying this issue, as it represents a serious medical and social problem that significantly limits the quality of life of patients. Exploring new mechanisms offers a promising path for developing innovative approaches to diagnosing and treating the combination of bronchial asthma and chronic obstructive pulmonary disease. It is important to note that only systematic clinical and functional monitoring of patients allows for an accurate diagnosis of chronic diseases. In our country, as well as worldwide, there is a growing trend of comorbid diseases of the bronchopulmonary and cardiovascular systems. The combination of bronchial asthma and COPD increases the risk of complications in the vascular bed of the small circulation, which, in turn, places this issue among the most urgent.